1990
DOI: 10.1111/j.1471-4159.1990.tb04975.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Changes in Nuclear Proteins Following Axotomy

Abstract: Changes in protein synthesis are thought to be important in the response of the neuron to axotomy. Certain axonally transported proteins whose synthesis increases probably play important roles in regeneration of the axon. Although little is known about the regulation of these changes, the cell often controls its production of proteins at the nuclear level, where transactivating proteins modulate the transcription of specific genes. Thus, changes in nuclear proteins might be expected to be among the early event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 26 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…1 This failure is due to both intrinsic 2 and extrinsic factors. [3][4][5] Most efforts to improve CNS axon survival and regeneration have focused on extrinsic factors, such as overcoming glial-associated inhibitors [6][7][8][9] or increasing deficient neurotrophic factor signaling. [10][11][12][13][14][15] Recent studies show axon regeneration can be promoted by differentially regulating intrinsic signaling molecules like PTEN, 16,17 SOCS3, 18 and the Krüppel-like family (KLF) family of transcription factors, 19,20 among others.…”
Section: Resultsmentioning
confidence: 99%
“…1 This failure is due to both intrinsic 2 and extrinsic factors. [3][4][5] Most efforts to improve CNS axon survival and regeneration have focused on extrinsic factors, such as overcoming glial-associated inhibitors [6][7][8][9] or increasing deficient neurotrophic factor signaling. [10][11][12][13][14][15] Recent studies show axon regeneration can be promoted by differentially regulating intrinsic signaling molecules like PTEN, 16,17 SOCS3, 18 and the Krüppel-like family (KLF) family of transcription factors, 19,20 among others.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies showed that a protein phosphatase activity associated with excised membrane patches from sensory neurons strongly counteracted PK A-me- Protein phosphatase (PP) activity was measured in the washed 100,000-g particulate fraction from .Aplysia abdominal ganglia successively extracted with homogenizing buffer containing 0 .5 M NaCl with phosphorylase a as a substrate in the presence and absence of 1-2. diated closure of S-K + channels (Shuster et al ., 1985(Shuster et al ., , 1986 . To identify the protein phosphatase associated with neuronal plasma membranes, ghosts of giant R2 and PLI cells were obtained by microsurgery (Buriani et al ., 1990) . The large size of these neurons (diameter of 800 N,m) allowed a portion of the plasma membrane to be excised under the microscope .…”
Section: Ppi Is the Major Membrane-bound Protein Phosphatase In Aplysmentioning
confidence: 99%
“…In RGCs, like other central nervous system (CNS) neurons, the failure to regenerate after injury or disease is multifactorial, including reduced intrinsic axon growth ability in adult neurons [2][3][4][5], tissue destructive inflammatory responses [6], extrinsic glial-associated inhibitory molecules [7][8][9], and insufficient neurotrophic factor support [10][11][12]. Most efforts to improve CNS axon survival and regeneration have focused on overcoming extrinsic glial-associated inhibitors in the injured CNS like Nogo, oligodendrocyte myelin glycoprotein (Omgp), semaphorin 3A, myelin associated glycoprotein, and chondroitin sulfate proteoglycans (CSPGs) [13][14][15][16][17][18][19], increasing deficient neurotrophic factor signaling [10,12,[20][21][22][23], modulating inflammation [24], and manipulating intrinsic signaling molecules like phosphatase and tensin homolog (PTEN) [25,26], SOCS3 [27], and the Krüppel-like family (KLF) family of transcription factors [28,29] among others well reviewed [30]. Addressing extrinsic factors individually or in combination with other extrinsic or intrinsic factors can slow RGC death, promote partial axon regeneration, and in some cases, restore limited visual function in animal models [26].…”
Section: Introductionmentioning
confidence: 99%